The rowing spine: A review of biomechanics, injury, and treatment - Cady-McCrea, C. I.; Lawlor, M. C.; Rodenhouse, T. F.; Puvanesarajah, V.; Mesfin, A. (World Neurosurgery, 2024)
Study Design Systematic literature review